Ubiquitous Electronic Health System - Rancang Bangun Smart Mouse dan Smart Watch Pengukur Denyut Jantung dan Suhu Tubuh - Muhammad Rizqy Alfarisi (Journal of Science and Applicative Technology, 2022)
The purpose of this research is to design a Ubiquitous Electronic Health System to monitor health during activities. The Ubiquitous Electronic Health System is a health monitoring system and facilitator of human health support devices that are applied to devices commonly used in everyday life such as mirrors, chairs, computer mice, watches, mobile phones, and others by utilizing the Photoplethysmograph method. The equipment developed in this study consisted of a computer mouse and a watch that was added with a photodiode, infrared, and a DS18b20 sensor with functionality as a heart rate detector and body temperature measurement. into the body but the measurement or screening action is carried out with the help of sensors attached to the skin, measurements are carried out in real-time when the equipment is used daily, the measurement results can be seen on the mobile phone screen and desktop applications, the data obtained from the measurement results can then be sent to the server to be stored as a user's medical record which can be used by the user to carry out further examinations to the doctor. The parameters that are the points in this study are the number of heart beats per minute and the measurement of body temperature, these two parameters are tested by comparing the results of tests carried out by tools designed with oximeters and thermometers. The test results from the Ubiquitous Electronic Health System tool provide an accuracy of up to 98% for measuring heart rate and 85% for measuring body temperature. Design and schematic have been shown in this study.